Interleukin-6 as a Biomarker for Breast Cancer Prognosis and Therapeutic Response - Seerwan Hamadameen Sulaiman; Hozan I. Ibrahim (QALAAI ZANIST JOURNAL, 2024)
The pleiotropic cytokine known as Interleukin-6 (IL-6) is a crucial component in the genesis and progression of breast cancer. It does this by acting on several signaling pathways at once, which has an impact on many different elements of tumor biology. The activation of signaling cascades that speed up cell cycle progression and prevent apoptosis is thought to be how IL-6 promotes tumor growth and proliferation. Furthermore, IL-6 promotes angiogenesis, which aids in the tumor’s development of additional blood vessels microenvironment. The proliferation, survival, and therapeutic resistance of cancer cells are all made possible downstream signaling pathways including JAK/STAT as well as MAPK are activated. Additionally, this cytokine promotes the epithelial-mesenchymal transition (EMT), further supporting tumor metastasis and invasion. Furthermore, within controlling immune responses and encouraging an immunosuppressive environment, IL-6 has an impact on the tumor microenvironment